Strategi Pembelajaran online di SMK Negeri 3 Bungo - Rahmat Hidayat (Pusat Riset dan Inovasi Nasional, 2023)
Strategy is a way or method that is chosen or it can also be interpreted as a way to achieve a goal in education. The definition of a learning strategy can be interpreted as a plan that contains a series of activities designed to achieve certain educational goals. The learning strategy includes specific learning approaches, models, methods and techniques. This research is a qualitative method, which is a method that aims to make a systematic, factual, accurate description, picture or painting of the properties and relationships between the phenomena investigated. In other words, descriptive research takes the problem or focuses on actual problems as they were at the time the research was carried out. What was collected was in the form of primary data and secondary data about teacher strategies in online learning, the techniques used in data collection were observations, interviews and documentation studies. Research leads to the methods used by teachers in online learning activities using platforms such as WhatsApp, email, and technology-based zoom.